Business model of optimal structure of management of transport and logistics centers - Tulendiev, Е.Е.; Baiguzhina, Г.Н.; Sagatbekova , А.Б.; Orazalina, А.Б. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
Transport logistics are transport enterprises that are participants in the process of distributing goods, aimed at obtaining a single economic result in the logistics chain. This article discusses the main factors of the company's productivity growth and the priority allocation system. The expansion of transport and logistics systems through the construction and modernization of transport and logistics centers at major transport hubs, mainly in regional centers, is also being considered. The expediency of the applied projects is proved using regression analysis based on the classical modeling method. Optimal management of the management of transport and logistics centers has a number of advantages over the traditional management method, and is also carried out by balancing the requirements of the main groups. The management model in the management of a transport and logistics center is based on five special management processes. In general, this analysis is a classical basic probability method, i.e. fully examines the economic indicators of the enterprise. The model is based on five special management processes. When studying the activities of the supply chain, a single plan provides for the intersection of the processes of supply of raw materials, product preparation, delivery and return, according to which the activities of all partner companies of the chain are coordinated Companies need to have a good understanding of their place in the supply chain and the possibilities for improving work efficiency.